Mitigating the Impacts of Development Corridors on Biodiversity: A Global Review - Juffe-Bignoli, Diego; Burgess, Neil D.; Hobbs, Jonathan; Smith, Robert J.; Tam, Christine; Thorn, Jessica P. R.; Bull, Joseph W. (Frontiers in Ecology and Evolution, 2021)
Development corridors are extensive, often transnational and linear, geographical areas targeted for investment to help achieve sustainable development. They often comprise the creation of hard infrastructure (i.e. physical structures) and soft infrastructure (i.e. policies, plans, and programmes) involving a variety of actors. They are globally widespread, and likely to be a significant driver of habitat loss. Here, we describe the development corridors phenomenon from a biodiversity perspective and identify the elements of best practice in biodiversity impact mitigation. We use these to carry out a review of the peer reviewed literature on corridors to respond to three questions: i) how impacts on biodiversity and ecosystem services are assessed; ii) what mitigation measures are discussed to manage these impacts; and iii) to what extent do these measures approximate to best practice. We found that of 271 publications on development corridors across all continents (except for Antarctica) mentioning biodiversity or ecosystem services, only 100 (37%) assessed impacts on biodiversity and 7 (3%) on ecosystem services. Importantly, only half of these (52, 19% of the total 271 articles) discussed mitigation measures to manage these impacts. These measures focused on avoidance and minimisation and there was scant mention of restoration or ecological compensation illustrating a deficient application of the mitigation hierarchy. We conclude that the academic literature on corridors does not give sufficient consideration to comprehensive mitigation of biodiversity impacts. To change this, impact assessment research needs to acknowledge the complexity of such multi-project and multi-stakeholder initiatives, quantify biodiversity losses due to the full suite of their potential direct, indirect and cumulative impacts, and follow all the steps of the mitigation hierarchy impact framework. We suggest a series of research avenues and policy recommendations to improve impact assessments of corridors towards achieving better biodiversity outcomes.